Enhancing immune regulation in vitro: the synergistic impact of 3′-sialyllactose and osteopontin in a nutrient blend following influenza virus infection - Guo, Zhengtao; Xie, Qinggang; Ren, Qiqi; Liu, Yang; Li, Kaifeng; Li, Bailiang; Li, Jufang (Frontiers in Immunology, 2024)
Natural components of breast milk, human milk oligosaccharides (HMOs) and osteopontin (OPN) have been shown to have a variety of functional activities and are widely used in infant formulas. However, the preventive and therapeutic effects of both on influenza viruses are not known. In this study, antiviral assays using a human laryngeal carcinoma cell line (HEP-2) showed that 3′-sialyllactose (3′-SL) and OPN had the best antiviral ability with IC50 values of 33.46 μM and 1.65 μM, respectively. 3′-SL (10 μM) and OPN (4 μM) were used in combination to achieve 75% inhibition. Further studies found that the combination of 200 μg/mL of 3′-SL with 500 μg/mL of OPN exerted the best antiviral ability. The reason for this was related to reduced levels of the cytokines TNF-α, IL-6, and iNOS in relation to mRNA expression. Plaque assay and TCID50 assay found the same results and verified synergistic effects. Our research indicates that a combination of 3′-SL and OPN can effectively reduce inflammatory storms and exhibit anti-influenza virus effects through synergistic action.